SPATIAL ANALYSIS OF TUBERCULOSIS, POPULATION AND HOUSING DENSITY IN YOGYAKARTA CITY 2017-2018 - Muthia Ardiyanti; Sulistyawati Sulistyawati; Yudha Puratmaja (Universitas Ahmad Dahlan, 2021)
Background: Tuberculosis (TB) is an infectious disease that becomes a health problem globally, including in Indonesia. Yogyakarta City is a district that struggle with TB; from 2017-2018, there was an increase of TB case in this city. There was limited evidence concerning TB and its possible risk factors among TB case 2017-2018, mainly using GIS in Yogyakarta.Methods: This study used an ecological study design to determine the correlation between population and housing density with TB incidence in Yogyakarta City in 2017-2018. Secondary data was obtained from the Yogyakarta City Health Profile 2018-2019. Â Spearman rank correlation test and spatial analysis using Quantum GIS software were employed to analyse the data.Results: There was a relationship between TB and population density variables (p-value = 0.034; R = -0.568) and housing density (p-value = 0.012; R = -0.625) in Yogyakarta, 2017-2018.Conclusions: This study indicates that the density of housings and population affect the prevalence of Tuberculosis.